Rendimento, valor nutritivo e qualidade sensorial de silagens de cereais de inverno elaboradas com diferentes cargas de compactação e filmes plásticos - Teixeira, Carlos Eugênio Fortes (2016)
Winter cereals are cultivated in order to produce grain for food and feed, or as fodder for cattle pasture. The objectives of this study were to analyze the production and chemical characteristics bromatological winter cereals, "pre-drying" or wilting, plastic films used in silages, compression loads and sensory analysis. For the field stage, the factorial arrangement of treatments 5 x 2 (5 cultivars and two cutting heights - low 7-10 cm, top 20 cm of soil surface) and the other in the experimental area of 0.5 ha. Several analyzes were carried out, it stands out: efficiency, nutritive value, pH and aerobic stability. The BRS Centauro oats is the most productive genotype in the form of silage in 2014 and BRS Serrano rye in 2015. There is no difference between genotypes for digestibility. The results density to imposed load, showed very different values. In the aerobic stability effect comparisons for types tested, there was only difference between LDPE (low density polyethylene) and polyester / vinyl and the latter showed greater time. There is the presence of acetic acid detected by sensory analysis, contributing to greater aerobic stability. For multiple comparisons for film types tested in oat silages BRS Centauro, the results show that the qualitative sensory attributes evaluated by rating corresponded to the quantitative attributes (pH) evaluated.